Dietary and supplementary management in the pathophysiology of polycystic ovary syndrome (Research, Society and Development, 2021)
Introduction: Polycystic Ovary Syndrome (PCOS) is a gynecological endocrine disorder that interferes with the process of ovulation and female fertility. Women with PCOS have the highest circulating androgen requirements related to Insulin Resistance (IR), dyslipidemia, obesity, gestational diabetes, Type 2 Diabetes Mellitus (DM II), Cardiovascular Disease (CVD) and Arterial Hypertension (SAH) and infertility. Objective: The aim of the present study was to address the beneficial effects of nutritional and supplemental therapy on PCOS and describe its pathogenesis, clinical manifestations and diagnosis. Materials and Methods: This is a non-systematic literature review of articles related to the topic of PCOS from the SciELO and Pubmed databases. Results and Discussion: The intervention in the lifestyle of the patient with PCOS is the most efficient form of treatment, especially in overweight women, with dietary management and inclusion of physical activity. And in this context, nutritional supplementation can be beneficial. Conclusion: Food plans with glycemic control and glycemic load control Insulin Resistance (IR), regressing the PCOS picture. In addition, nutritional supplementation of myoinusitol and vitamin D may contribute to the control of PCOS signs and symptoms.